Transformations on knowledge representation between OWL and RDF knowledge graphs: a study case - Ferreirone, Mariano (2023)
Is well known that the semantic web is having a tremendous impact on many aspects of the world and that it’s a wave that is far away from going down. Ontology and Knowledge graphs are two methods of knowledge representation that are part of the basis of this wave, and both have their pros and cons. In this work, there is an analysis over the relation between a rigid schema knowledge representation as OWL, and a simple and more flexible one like RDF. This is based on the attempt of transforming an OWL knowledge graph into an RDF knowledge graph, taking into account the interesting possibility of combining knowledge graphs that were created with different levels of schema formalization. The work also presents a case of study on the chess domain.